Theoretical and Methodological Analysis of Workaholism in the Context of Addictive Behavior - Onopchenko, Iryna (Psychological Prospects Journal, 2018)
The article examines workaholism as the problem in modern society. It’s a huge problem because uncontrolled growth of competitiveness and high requirements for workers cause fierce competitions for workplaces and struggles for possibilities of career development. Despite that, the problem of work addiction is still unadmitted. Workaholism is a complex social psychological problem, where complexity consists of ambivalent attitude of people to it. Also, many companies popularize workaholism as benefit. The article analyzes the latest researches of work addiction in our country and the world. You can find stages of addictive behavior and read characteristic of workaholism at any of them here. Moreover, the personality of workaholics was put to the test too. Article has special study of thier communication with society, self-esteem, attitude to work and attitude to rest. You can see differences between workaholics and normal people, who just love their jobs without any psychological addictions in this paper. Also, common features of workaholism and manifestation of this addiction at each stage were described here. There are described psychological features of this addiction type’s formation, addict’s attitude to his surroundings, noted changes in addict’s personality, his attitude to problem and emotions which person passes through while being in addiction’s influence. You have an opportunity to watch how a person, while wanting to feel better, without making any effort to change a situation sacrificing himself to the disease that gives him what he wants and then takes everything away. As further research perspective we see detailed consideration of work addictions not described in this article, such as urgent addiction and perfectionism, and also studying of workaholism origins through the prism of early dysfunction schemes theory by J. Young.